Estudo das respostas dos astrócitos hipotalâmicos ao tratamento in vitro com ácidos graxos saturados - Oliveira, Ariadne de Almeida Branco (2015)
High-fat diets induce the formation of inflammatory signals in the hypothalamus which reduces their ability to respond to the hormones leptin and insulin, involved with the control of satiety and food intake. The hypothalamus contains a large amount of glial cells highlighting the astrocytes, which are incorporated in heterogeneous groups of neurons that participate in the control circuit of energy homeostasis, additionally, they are involved in various processes, including the neuroinflammation. In this sense, the present study aimed to investigate the role of hypothalamic astrocyte responses in front of excess fatty acids and the interaction of these cells with neurons of the hypothalamus. For that, we used primary cell cultures of hypothalamic astrocytes and primary cultures of hypothalamic neurons. The medium removed from astrocyte cultures treated with fatty acid (estereato or palmitate) or LPS (positive control) was used on neuronal cultures for further in vitro study of synaptogenesis, also, measurement of cytokines present in conditioned medium was performed with the CBA kit mouse-Th1 /Th2/Th17 by flow cytometry with the aim of analyzing the profile of inflammatory response considering the different treatments. In front of this result, we have seen that the treatment with fatty acid promoted a profile of Th2 response (anti-inflammatory), especially when compared to Th1 profile (pro-inflammatory) of the LPS control. After the treatment, the total RNA of astrocytes was extracted for the sequencing of transcripts by RNA-Seq. Through the analysis of the genes differentially expressed between the groups, it was observed that treatment with fatty acid induced an inflammatory response, however, with lesser intensity in relation to treatment with LPS, and, at the same time, some genes related to neuroprotection were more expressed in astrocytes treated with fatty acid, collaborating with the data of the CBA. The culture of neuron was standardized in our laboratory and, subsequently, treated with conditioned medium. By immunostaining, we observed that treatment with the conditioned medium in astrocytes treated with fatty acids reduced the total synaptic density, primarily affecting excitatory synapses, on the other hand, the number of neurons was similar between treatments, however, with the presence of a reduced number of pyknotic nuclei after the treatment with fatty acids. These results suggest an active role of astrocyte in inflammation induced by the excess of fatty acids, participating in the modulation of the inflammatory response, apparently, with neuroprotective effects.